2020
DOI: 10.1136/bmjdrc-2020-001465
|View full text |Cite
|
Sign up to set email alerts
|

Expression of clock geneDbpin omental and mesenteric adipose tissue in patients with type 2 diabetes

Abstract: IntroductionWe previously reported in ob/ob mice, one of animal models of human type 2 diabetes mellitus (DM2), that (i) acetylation of histone H3 lysine 9 (H3K9) at the promoter region of clock gene Dbp and DBP mRNA expression are reduced in epididymal adipose tissue, (ii) binding of DBP to the promoter region of peroxisome proliferator-activated receptor (Ppar)-γ and mRNA expression of PPAR-γ1sv were decreased in preadipocytes and (iii) adiponectin secretion was decreased, leading to the impaired insulin sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We identified Dbp and its homologs Tef and Hlf as potential master regulators of the upregulated rhythmic pathway. Dbp is a transcription factor with expression under circadian control ( Zvonic et al, 2006 ) and has been reported to improve insulin sensitivity and enhance adipogenesis in pre-adipocytes of vWAT in mice and humans ( Suzuki et al, 2019 ; Ushijima et al, 2020 ). Taken together, we hypothesize that training-induced increases in circadian rhythm gene expression via Dbp may contribute to hyperplasia in WAT.…”
Section: Discussionmentioning
confidence: 99%
“…We identified Dbp and its homologs Tef and Hlf as potential master regulators of the upregulated rhythmic pathway. Dbp is a transcription factor with expression under circadian control ( Zvonic et al, 2006 ) and has been reported to improve insulin sensitivity and enhance adipogenesis in pre-adipocytes of vWAT in mice and humans ( Suzuki et al, 2019 ; Ushijima et al, 2020 ). Taken together, we hypothesize that training-induced increases in circadian rhythm gene expression via Dbp may contribute to hyperplasia in WAT.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of Dbp was reported to ameliorate insulin sensitivity via direct binding to the promoter region of Pparg, driving mRNA expression of a splicing variant of Pparg (Ppar-γ1sv), and enhancing adipogenesis in preadipocytes from ob/ob mice vWAT 75 . Promoter activity of Dbp as reflected by histone H3 lysine 9 acetylation (H3K9ac) levels, and Dbp and Pparg expression in omental adipose tissue, were reported to be decreased in patients with T2D 76 . Our results suggest that exercise-induced circadian rhythm gene expression changes regulated by Dbp may contribute to adipogenesis of ASCs in WAT.…”
Section: Discussionmentioning
confidence: 99%
“…Increased H3K9me3 in the Slc2a4 promoter could reduce the expression of GLUT4, encoded by Slc2a4, which contributes to glycemic impairment in T2D (15). Acetylation of H3K9 at the promoter region of clock gene Dbp and DBP mRNA expression in omental adipose tissue, a compartment related to the mechanism of T2D, was significantly lower in T2D patients (112).…”
Section: Type 2 Diabetesmentioning
confidence: 99%